Development of the Baby Monster Notes Game to Enhance Music Note Reading Skills of Grade 4 Students at Sarasas Witaed Patcharamonthon School - ไพโรจน์, นิติศักดิ์; บุญทา, จุฑามาศ; อมรธีระกุล, ปัทมวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were: 1. to develop the music note reading skills of Grade 4 students using the Baby Monster Notes game, and 2. to study students’ satisfaction toward the learning management of music note reading using the Baby Monster Notes game.           The sample group consisted of 32 Grade 4 students selected through purposive sampling. The research instruments included: 1) lesson plans for music note reading using the Baby Monster Notes game, 2) a pre-test and post-test on music note reading skills, and 3) a questionnaire on students’ satisfaction toward the use of the Baby Monster Notes game in learning management.           The researcher implemented learning activities using the Baby Monster Notes game for 8 instructional periods. A pre-test and post-test were administered, and the scores were compared. The statistical methods used for data analysis were mean, standard deviation, and t-test.           The results revealed that students’ music note reading skills after the learning activity were significantly higher than before the learning activity. This indicated that students’ music note reading skills improved after participating in the learning activities using the Baby Monster Notes game. Regarding students’ satisfaction toward the use of the Baby Monster Notes game, the overall satisfaction level was at the highest level, with a mean score of 4.68. This reflects that the game was appropriate for the learners’ age, motivated their learning, and increased their interest in practicing music note reading skills, resulting in more effective learning.